Train from Marietta - Garlock, Dorothy (New York : Warner Books, 2006)
When Kate Tyler is kidnapped by a band of outlaws while on a cross-country trip, cowboy Tate Castle rescues Kate and hides her at the remote ranch where he lives with his five -year-old, disabled daughter.
Keywords: Kidnapping victims -- Fiction; Children with disabilities -- Fiction; Ranch life -- Fiction; Cowboys -- Fiction; Texas -- Fiction; Romantic suspense fiction; Western stories